Pulsed-Metal Organic Chemical Vapor Deposition (PMOCVD) for Growth of Single Phase Wurtzite MgxZn1-xO Epitaxial Film with High Mg Content (x=0.51). Issue 4 (2016) - Alema, Fikadu; Ledyaev, Oleg; Miller, Ross; Beletsky, Valeria; Osinsky, Andrei; Schoenfeld, Winston V.
ABSTRACT: Pulsed metal organic chemical vapor deposition (PMOCVD) was used to grow high Mg content, high quality, wurtzite Mgx Zn1-x O (MgZnO) epitaxial film to realize photodetectors and emitters in the solar blind spectral window. MgZnO films with various Mg contents were deposited on c-plane Al2 O3 with and without AlN buffer layer. The band gap of the films range from 3.24 eV to 4.49 eV, corresponding to fraction of Mg between x =0.0 to x =0.51, as determined by Rutherford backscattering spectroscopy (RBS). Cathodoluminescence (CL) measurement showed a linear blue shift in the spectral peak position of Mgx Zn1-x O with an increase in x . No multi-absorption edge or CL band splitting was observed, indicating the phase purity of the films and was confirmed by XRD analysis. The surface quality of the films has improved with the increase in Mg content. To the best of our knowledge, the current result shows the highest Mg content ( x =0.51), high quality, single phase wurtzite MgZnO epitaxial film ever grown by MOCVD. This is realized due to the non-equilibrium behavior of PMOCVD in which radicals that are formed during the growth process will have insufficient time to reach equilibrium.